2009
DOI: 10.1002/ab.20327
|View full text |Cite
|
Sign up to set email alerts
|

Could mindfulness decrease anger, hostility, and aggression by decreasing rumination?

Abstract: Research suggests that rumination increases anger and aggression. Mindfulness, or present-focused and intentional awareness, may counteract rumination. Using structural equation modeling, we examined the relations between mindfulness, rumination, and aggression. In a pair of studies, we found a pattern of correlations consistent with rumination partially mediating a causal link between mindfulness and hostility, anger, and verbal aggression. The pattern was not consistent with rumination mediating the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
123
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(157 citation statements)
references
References 92 publications
21
123
1
3
Order By: Relevance
“…This may be because most of this evidence is based on training in state mindfulness rather than trait mindfulness differences (e.g., Deyo et al 2009;Heeren and Philippot 2011;Kingston et al 2007). Although Borders et al (2010) reported an association with trait mindfulness, they measured mindfulness with the Mindfulness Attention Awareness Scale (Brown and Ryan 2003) and this scale has more in common with measures of attentional cognitive failures than with other measures of trait mindfulness (Cheyne, Carriere and Smilek 2006;Grossman 2011). So it seems that something specific to the skills taught in mindfulness training programmes might be crucial to reducing rumination.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because most of this evidence is based on training in state mindfulness rather than trait mindfulness differences (e.g., Deyo et al 2009;Heeren and Philippot 2011;Kingston et al 2007). Although Borders et al (2010) reported an association with trait mindfulness, they measured mindfulness with the Mindfulness Attention Awareness Scale (Brown and Ryan 2003) and this scale has more in common with measures of attentional cognitive failures than with other measures of trait mindfulness (Cheyne, Carriere and Smilek 2006;Grossman 2011). So it seems that something specific to the skills taught in mindfulness training programmes might be crucial to reducing rumination.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has pointed to more adaptive forms of rumination involving reflection (which involves actively turning inward, with thoughts centering around self-focus, problem-solving, and coping) that may not necessarily be problematic (Treynor, Gonzalez, & Nolen-Hoeksema, 2003;Watkins, 2004). In addition, some individuals may have a greater capacity for cognitive flexibility or for giving their full attention to the present moment (i.e., engaging in mindfulness), and these processes may buffer against negative emotions (e.g., Borders, Earleywine, & Jajodia, 2010). Future research could explore the link between surveillance behaviors and relational satisfaction with a focus on possible cognitive-process mediators, such as helpful cognitions and mindfulness approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness is strongly linked with reduced negative affect [42] and can reduce anger and aggression [43].…”
Section: Improved Outlook Pain Reliefmentioning
confidence: 99%